Identification and discrimination of vowel duration - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
The identification and discrimination of vowel duration was investigated. The experimental results could not be unambiguously interpreted in favour of either categorial or continuous perception of the acoustic variable under study. Furthermore, the subjects’ response bias in the discrimination test was examined. It turned out that the number of "false alarms" (i.e. "different" responses to pairs of physically identical stimuli) varied in a systematic manner, being considerably higher near the phoneme boundary (as established by identification tests) than within the phoneme areas. It is attempted to explain the systematic variation of response bias in terms of Fujisaki and Kawashima’s model of the decision process in discrimination tasks.